The Thought And Methodology Of Imam An-Nasa'i In Writing Sunan An-Nasa'i - Ananda, M Wahyu; Yolla, Desni Febri (Journal of Innovation in Research, Education and Culture (JIREC), 2025)
The present article aims to discuss Imam An-Nasa'i's thinking and methodology in writing Sunan An-Nasa'i, one of the six major hadith books in the Islamic tradition. The introduction delineates the significance of Sunan An-Nasa'i in the compilation of authentic hadith, while also underscoring Imam An-Nasa'i's stature as a preeminent scholar in the discipline of hadith. The intellectual framework and methodological approach employed by Imam An-Nasa'i exerted a profound influence on his methodology of collecting, filtering, and compiling hadith. The research method employed is a qualitative literature study, wherein relevant texts were analyzed, including Sunan An-Nasa'i and other works that discuss Imam An-Nasa'i's methodology. This approach entails a comprehensive examination of the criteria employed in the selection of hadith, the methodology utilized in the assessment of its authenticity, and the systematic arrangement of chapters and themes within the book. The results indicate that Imam An-Nasa'i employs a rigorous methodology in the selection of hadith, incorporating only those that meet specific quality criteria, particularly with regard to the integrity of the sanad and the credibility of the narrators. Additionally, he prioritizes hadith that are more robust in terms of chain of transmission and less in terms of repetition of hadith found in other sources. This approach has led to the recognition of Sunan An-Nasa'i for its meticulous selection and its high scholarly value. Keywords: Imam An-Nasa'i, Methodology, Sunan An-Nasa'i, Hadith.